Ufundishaji wa fasihi : nadharia na mbinu - Njogu, Kimani; Chimerah, Rocha M.; Kiswahili Tertiary Publishing Project (Kenya) (Nairobi : Jomo Kenyatta Foundation, 1999)
The concept and methods of teaching Swahili literature.
"Ensaiklopidia ya ufundishaji wa fasihi"--Cover.
"Kiswahili Tertiary Publishing Project"--Colophon
Includes bibliographical references (p. 386-392) and index.
In Swahili.
Keywords: Swahili literature -- Study and teaching